EVALUATING THE EFFECTIVENESS OF ANATOMY AND HISTOLOGY PRACTICUM DURING COVID-19 PANDEMIC AT FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS WARMADEWA - Evayanti, Luh Gde; Sumadewi, Komang Trisna; Witari, Ni Putu Diah; Suka Astini, Dewa Ayu Agung Alit; Kerans, Fransiscus Fiano Anthony; Dewi, A.A.Ayu Asri Prima; Ekayani, Ni Wayan Diana (E-Jurnal Medika Udayana; Vol 13 No 6 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i06.P11, 2024)
The implementation of anatomy and histology practical sessions at Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Universitas Warmadewa during the Covid-19 pandemic still has many variations. This difference in implementation will have an influence on the achievement of student learning. This research aims to evaluate the knowledge of anatomy and histology among students by giving asynchronous learning, pre-test, post-test and practicum exam. This study using cross-sectional approach. 124 participants are 3th semester students whose active status at FKIK Universitas Warmadewa. The primary data were collected directly from practical sessions and practicum exam. The pre-test and post-test data were analyzed using paired-T test (p<0.05). The post-test and practicum exam were analyzed using Spearman rho (p<0.05). In anatomical practicum, there is an increase in post-test scores when compared to pre-test although not significant (p = 0.119). Anatomical practicum exam results have a meaningful positive correlation with post-tests (p = 0.013, r = 0.22). In histological practicum there was a significant increase in post-test scores when compared to pre-tests (p = 0.013), although practicum exam results were not significantly correlated with post-test (p = 0.410). Based on this study, improvements are needed related to technical of anatomical and histological practicums, as well as provisions related to practicums so that activities are structured